Chemistry versus physics : chemical reactions near critical points - Gitterman, M. (World Scientific Pub. Co., 2010)
Chemical reactions at high pressures are widely used in modern technology (supercritical extraction is an example). On the other hand, critical phenomena is the more advanced field in statistical mechanics. There are thousands of theoretical and experimental articles published by physicists, chemists, biologists, chemical engineers and material scientists, but, to our knowledge, there are no books which link these two phenomena together. This book sums up the results of 222 published articles, both theoretical and experimental, which will be of great benefit to students and all researchers working in this field.